2019
DOI: 10.22159/ajpcr.2018.v12i1.30094
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Investigation of Anthelmintic, Antibacterial and Antifungal Activity of 3,3-Diphenyl Propanamide Derivatives

Abstract: Objective: A novel series of substituted 3,3-diphenyl propanamide derivatives (I-VIII) were synthesized by reacting 3,3-diphenyl propanoyl chloride with different amines/amino acids, and all the derivatives were investigated for anthelmintic, antibacterial, and antifungal activity.Methods: All the compounds were characterized by infrared (IR) and1H- nuclear magnetic resonance spectrometry data. The synthesized derivatives were investigated for their anthelmintic activity employing housefly worms method and ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In another investigation conducted by Sachin Chaudhary (2019), it was observed that propenamide, when administered at a concentration of 50 µg/mL, demonstrated the highest level of efficacy against Gramnegative bacterial strains. Notably, these strains included Escherichia coli and Pseudomonas aeruginosa, outperforming the effects of ciprofloxacin [20]. Yasir et al (2017) reported that propenamide exhibited robust inhibition against Bacillus subtilis and Escherichia coli, displaying zone of inhibition measurements of 16 mm for both bacterial strains [21].…”
Section: Discussionmentioning
confidence: 99%
“…In another investigation conducted by Sachin Chaudhary (2019), it was observed that propenamide, when administered at a concentration of 50 µg/mL, demonstrated the highest level of efficacy against Gramnegative bacterial strains. Notably, these strains included Escherichia coli and Pseudomonas aeruginosa, outperforming the effects of ciprofloxacin [20]. Yasir et al (2017) reported that propenamide exhibited robust inhibition against Bacillus subtilis and Escherichia coli, displaying zone of inhibition measurements of 16 mm for both bacterial strains [21].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed by one-way analysis of variance (ANOVA) followed by Dunnett'st-test. At 95% confidence interval, p values<0.001 were considered significant [31].…”
Section: Discussionmentioning
confidence: 99%
“…The docking parameters used were as follows: GA population size = 100 and the maximum number of energy evaluation = 2,500,000, other parameters used were default values. The lowest binding energy conformation was searched out and used for further analysis [29][30][31].…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…This is known for its use in the relief of arthritis pain. Long-term use of NSAIDs leads results in gastrointestinal ulceration, bleeding and nephrotoxicity 18,20 . The gastrointestinal damage is generally associated with two factors which include local irritation by carboxylic acid moiety, which is common in most NSAIDs (topical effect) and decreased the production of tissue prostaglandin (PGs), which minimizes the physiological role of cytoprotective prostaglandins in maintaining GI health and homeostasis 21 .…”
mentioning
confidence: 99%
“…Studies showed that forming the derivative of the carboxylate function of representative NSAIDs resulted in an enhanced anti-inflammatory activity with reduced ulcerogenic effect. Moreover, certain compounds bearing 1, 3, 4-oxadiazole/thiadiazole and 1, 2, 4-triazole nucleus have been reported to bear significant anti-inflammatory activity 19,20 . In the last two decades, there has been a considerable amount of work in the role of reactive oxygen species in inflammation.…”
mentioning
confidence: 99%